2011
DOI: 10.1194/jlr.m015263
|View full text |Cite
|
Sign up to set email alerts
|

Role of the AMPK/SREBP-1 pathway in the development of orotic acid-induced fatty liver

Abstract: been used as a chemical inducer of fatty liver ( 2, 3 ). Although somewhat inconclusive, the reported mechanisms of OA-induced fatty liver include impairment of fatty acid oxidation, stimulation of lipogenesis, and reduction in lipid transport from the liver ( 4, 5 ). OA-induced fatty liver is species specifi c, and thus far, only the rat has been found to be susceptible. Durschlag and Robinson demonstrated that pharmacokinetic factors determined species specifi city in OA-induced hepatotoxicity ( 6 ). However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
67
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 92 publications
(73 citation statements)
references
References 49 publications
6
67
0
Order By: Relevance
“…Consistent with our observation, orotate was reported to induce fatty liver in rodents more than half a century ago ( 41 ), but the precise mechanism has yet to be delineated ( 42 ). Our data suggest that orotate causes fatty liver by impairing hepatic mitochondrial respiration via inhibition of DHODH enzymatic activity.…”
Section: Discussionsupporting
confidence: 80%
“…Consistent with our observation, orotate was reported to induce fatty liver in rodents more than half a century ago ( 41 ), but the precise mechanism has yet to be delineated ( 42 ). Our data suggest that orotate causes fatty liver by impairing hepatic mitochondrial respiration via inhibition of DHODH enzymatic activity.…”
Section: Discussionsupporting
confidence: 80%
“…However, OA treatment to these cells reversed the effects of LKB1, as observed by decreased raptor phosphorylation and increased p70S6K1 phosphorylation. These results are in line with our data, wherein we observed proteasomal degradation of LKB1 and subsequent attenuation of AMPK phosphorylation by OA in LKB1-overexpressed HeLa cells (Jung et al, 2011).…”
Section: Oa-induced Cell Proliferation Is Attenuated By Ampk Activationsupporting
confidence: 93%
“…While many studies have demonstrated the properties of OA as a tumor promoter, few have provided evidence and understanding of the molecular mechanisms of OA-induced cell proliferation. Recently we reported that OA induces fatty liver mediated by mTOR activation (Jung et al, 2011). Based on these results, we hypothesized that OA-induced mTOR activation could contribute to the cell proliferation.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…For Oil Red-O staining, frozen liver tissues were cut into 7 mm and affixed to microscope slides. Sections were reacted with Oil Red-O solution buffer and counterstained with Harris hematoxylin as described (Jung et al, 2011).…”
Section: Histologic Analysis and Oil Red-o Stainingmentioning
confidence: 99%